Molecular Characterization and Epidemiology of Carbapenem-Resistant Enterobacteriaceae Isolated from Pediatric Patients in Guangzhou, Southern China - Fei Gao; Zhile Xiong; Bingshao Liang; Zhenting Huang; Qiulian Deng; Jielin Wang; Huamin Zhong; Yan Long; Sufei Zhu (Canadian Journal of Infectious Diseases and Medical Microbiology, 2023)
Background. Carbapenem-resistant Enterobacteriaceae (CRE) are spreading worldwide, posing a serious public health concern. However, the data on CRE strains that cause infections in children in Guangzhou remain limited. Therefore, this study aimed to investigate the epidemiology of CRE, drug resistance, and resistance mechanisms in children in Guangzhou, Southern China. Methods. In total, 54 nonrepetitive CRE strains were collected in pediatric patients at three centers in Guangzhou, Southern China, from January 2016 to August 2018. CRE isolates were used for further studies on antimicrobial susceptibility, the modified Hodge test (MHT), the modified carbapenem inactivation method (mCIM), and drug resistance genes. Multilocus sequence typing (MLST) was used to elucidate the molecular epidemiology of K. pneumoniae. Results. The isolated CRE strains include 34 K. pneumoniae (63.0%), 10 E. coli (18.5%), 4 Enterobacter cloacae (7.4%), and 6 Proteus mirabilis (11.1%) strains. The strains were isolated mainly from the blood (31.5%, n = 17), sputum (31.5%, n = 17), and urine (16.7%, n = 9). All CRE isolates were highly resistant to the third- or fourth-generation cephalosporins, carbapenems, and β-lactam + β-lactamase inhibitors (94.4%–96.3%). In addition, the resistance rates to amikacin, ciprofloxacin, levofloxacin, tigecycline, and colistin were 5.6%, 14.8%, 16.7%, 9.3%, and 0%, respectively. Carbapenemase was detected in 35 (64.8%) of the CRE isolates. The most dominant carbapenemase gene was blaNDM (n = 17, 48.6%), followed by blaIMP (n = 13, 37.1%) and blaOXA-23 (n = 4, 11.4%). Other carbapenemase genes (blaKPC, blasim, blaAim, blaGES, blaGim, blaOXA-2, and blaOXA-48) and the mcr-1 gene were not detected. MLST analysis showed high diversity among the K. pneumoniae, and ST45 (11.7%, 4/34) was the dominant sequence type. Conclusion. This study revealed blaNDM was the most dominant carbapenemase gene in children in Guangzhou. Infection control measures need to be taken for the prevention and treatment of CRE infections.